Implementasi Media Gambar Berseri untuk Peningkatan Kemampuan Menulis Karangan Narasi Siswa Kelas V SD Negeri Lae Saga - Pujiyanti Pujiyanti; Friska Ria Sitorus; Wahyu Ningsih (Universitas Muhammadiyah Surabaya, 2026)
This study aims to improve the ability to write narrative essays of fifth grade students of SD Negeri Lae Saga Subulussalam City through the implementation of serialized picture media. The research method used is Classroom Action Research (PTK) with two cycles, each of which consists of planning, implementation, observation, and reflection stages. The subjects of this study were 20 grade V students in the 2024-2025 school year. The instruments used included observation sheets, interview guidelines, and writing tests. The results showed that the use of serialized images can improve students' narrative writing skills, especially in terms of completeness of structure, use of vocabulary, and accuracy of spelling and punctuation. In cycle I, students' learning completeness reached 50%, then increased to 90% in cycle II. This finding shows that serialized picture media is effective in stimulating imagination and making it easier for students to compose stories coherently and creatively. Thus, this media is worth applying as an alternative in learning writing in elementary schools to improve the quality of students' language skills.